Improved Helicobacter pylori Eradication Rate of Tailored Triple Therapy by Adding Lactobacillus delbrueckii and Streptococcus thermophilus in Northeast Region of Thailand: A Prospective Randomized Controlled Clinical Trial - Taweesak Tongtawee; Chavaboon Dechsukhum; Wilairat Leeanansaksiri; Soraya Kaewpitoon; Natthawut Kaewpitoon; Ryan A. Loyd; Likit Matrakool; Sukij Panpimanmas (Gastroenterology Research and Practice)
Background and Aim. To evaluate the effect of Lactobacillus delbrueckii subsp. bulgaricus and Streptococcus thermophilus to Helicobacter pylori eradication in different periods of therapeutic protocol. Methods. Infected patients were randomized to one-week tailored triple therapy (esomeprazole 20 mg bid, clarithromycin 500 mg bid/metronidazole 400 mg tid if clarithromycin resistant, and amoxicillin 1000 mg bid) with placebo (group 1, n=100); one week of pretreatment with probiotics (group 2, n=100); and one week of pretreatment with probiotic followed by one week of the same probiotics after treatment (group 3, n=100). Result. PP analysis involved 292 patients, 98 in group 1, 97 in group 2, and 97 in group 3. Successful eradication was observed in 229 patients; by PP analysis, the eradication rates were significantly higher (P<0.01, 95% CI; 0.71–0.97) in group 2 and group 3 than group 1. ITT analysis eradication rates were significantly higher in group 2 and group 3 than group 1 (P<0.01 95% CI; 0.72–0.87), and there is no significant difference between the three groups (P=0.32) in terms of adverse events. Conclusion. Adding probiotics before or before and after tailored treatment can improve Helicobacter pylori eradication rates. This trial is registered with Thai Clinical Trials Registry number: TCTR20141209001.